Forging C–C Bonds through Intramolecular Oxidative Coupling of Organoborates – An Overview - Didier, Dorian (Synthesis, 2022)
C–C bond formation has challenged the community of synthetic organic chemists for decades. Organoboron derivatives represent a mild and functional-group-tolerant class of reagents that can be handled without the need for inert conditions, making them suitable scaffolds for the development of methods that increase the sustainability of current processes for coupling reactions. This short review summarizes the different approaches that have been developed to enable C–C bond formation through intramolecular rearrangements of organoborate species.1 Introduction2 Oxidative Coupling with Chemical Oxidants3 Electrocoupling of Tetraorganoborates4 Photocoupling of Tetraorganoborates
Keywords: C–C bond formation; electrochemistry; photocatalysis; oxidative coupling